2022
DOI: 10.1111/nup.12403
|View full text |Cite
|
Sign up to set email alerts
|

Bring me my alcohol!—On the continuum of pleasure and pain

Abstract: Alcohol use has been recognized as a challenge in eldercare and social care, and some anticipate that problems related to alcohol use will increase in the future as the current adult generation has high alcohol consumption rates. Accordingly, it is suggested that care workers are at risk of becoming passive bystanders to the destructive lifestyles of vulnerable older adults and even facilitating these lifestyles. In the present paper, we suggest that alcohol exacerbates and underscores inherent difficulties in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Thus, our findings present an argument against therapeutic nihilism that has otherwise been associated with AUD in older adults (O'Connell et al, 2003; Wadd & Dutton, 2018). Studies have shown that healthcare professionals may be tempted to not address excessive alcohol use in the older population based on the assumption that the pleasure of drinking alcohol should not be removed from older men and women, since they may not have much pleasure left in life (Christiansen & Nielsen, 2023; O'Connell et al, 2003). However, in our study, the QoL of older adults suffering from AUD does not decline following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings present an argument against therapeutic nihilism that has otherwise been associated with AUD in older adults (O'Connell et al, 2003; Wadd & Dutton, 2018). Studies have shown that healthcare professionals may be tempted to not address excessive alcohol use in the older population based on the assumption that the pleasure of drinking alcohol should not be removed from older men and women, since they may not have much pleasure left in life (Christiansen & Nielsen, 2023; O'Connell et al, 2003). However, in our study, the QoL of older adults suffering from AUD does not decline following treatment.…”
Section: Discussionmentioning
confidence: 99%